Truncations in the X-Ray Halos of Early-type Galaxies as a Tracer of Feedback and Mergers - Nushkia Chamba; Pamela M. Marcum; Alejandro S. Borlaff; Pasquale Temi; Aneta Siemiginowska (The Astrophysical Journal)
The morphology of X-ray halos in early-type galaxies depends on key structure assembly processes, such as feedback and mergers. However, the signatures of these processes are difficult to characterize due to their faint and amorphous nature. We demonstrate that the truncation in the temperature profile of X-ray halos, defined by the radial location of the peak temperature, is significantly more impacted by recent mergers or galaxy interactions than feedback processes. At a fixed stellar mass, a highly asymmetric X-ray halo can be nearly a factor of 10 more truncated than a relaxed one. This analysis led to a discovery of previously unknown asymmetric features in the optical and X-ray halos of three massive galaxies. We detect the intra-group star light and a large ∼45 kpc size stellar stream connected to NGC 0383, suggesting that a recent stellar accretion event has triggered its active galactic nuclei to emit a powerful radio jet. While the disturbed X-ray halo of NGC 1600 is also related to a galaxy-satellite tidal interaction detected in optical imaging, the X-ray shape and asymmetry of NGC 4555 are highly unusual for a galaxy in a low-density environment, requiring further investigation. These results highlight the importance of truncations and deep imaging techniques for untangling the formation of X-ray halos in massive galaxies.